2013
DOI: 10.1186/1752-153x-7-164
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking simulation studies on potent butyrylcholinesterase inhibitors obtained from microbial transformation of dihydrotestosterone

Abstract: BackgroundBiotransformation is an effective technique for the synthesis of libraries of bioactive compounds. Current study on microbial transformation of dihydrotestosterone (DHT) (1) was carried out to produce various functionalized metabolites.ResultsMicrobial transformation of DHT (1) by using two fungal cultures resulted in potent butyrylcholinesterase (BChE) inhibitors. Biotransformation with Macrophomina phaseolina led to the formation of two known products, 5α-androstan-3β,17β-diol (2), and 5β-androstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The absorbance at 3408 cm −1 , confirmed the existance of a hydroxyl group. Melting point, 13 C-NMR and 1 H-NMR spectral data, assignments and chemical shifts for this compound were in agreement with those which have been reported by Zafar et al in 2013 for 12β-hydroxyandrost-1,4-dien-3,17-dione [ 19 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The absorbance at 3408 cm −1 , confirmed the existance of a hydroxyl group. Melting point, 13 C-NMR and 1 H-NMR spectral data, assignments and chemical shifts for this compound were in agreement with those which have been reported by Zafar et al in 2013 for 12β-hydroxyandrost-1,4-dien-3,17-dione [ 19 ].…”
Section: Resultssupporting
confidence: 90%
“…This compound which is significant and specific inhibitor of butyrylcholinesterase (BChE), in comparison to standard drug, galanthamine. 12β-hydroxyandrost-1,4-diene-3,17-dione (IV) was also another hydroxylated steroid which has been obtained from DHT biotransformation by G. fujikuroi [ 19 ]. Although hydroxylation of steroidal substrates is common by filamentous fungi, hydroxylation at C-12 position is relatively rare [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The redocking step has been widely implemented for efficient molecular docking calculations. 19,20 The analysis was carried out on the TES coordinates as a reference for the cocrystals. The coordinates showed that the position of TES is in the pocket of the HSD17B1 enzyme (Fig.…”
Section: Molecular Docking: Superposition and Inhibitor-hsd17b1 Confo...mentioning
confidence: 99%
“…Molecular docking provides good calculation efficiency for inhibitor coordination on the enzyme active site. 19,20 Meanwhile, the MD simulation offers a comprehensive analysis of the interaction between an inhibitor and the targeted protein during the simulation time. 17,21 The evaluation proceeds by several considerations, such as grid-score 20 and binding free energy, 22 aiming to see the binding affinity of inhibitor to HSD17B1.…”
Section: Introductionmentioning
confidence: 99%
“…This system has been associated with a number of cognitive functions, including memory and emotional processing. To date, a number of in vitro studies on inhibitory effects of various steroidal molecules have been carried out, and some of them have been identified as weak or strong inhibitors of these cholinesterases (Richmond et al ., 2013; Zafar et al ., 2013; Yusop et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%